UNIQUE CONFORMATION OF RH(I) PILLAR COMPLEXES IMMOBILIZED ON TAENIOLITE - Kiky C. Sembiring; Shogo Shimazu (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2011)
UNIQUE CONFORMATION OF RH(I) PILLAR COMPLEXES IMMOBILIZED ON TAENIOLITE. Rhodiumpillar complex with chiral diamine ligands, Rh-Cn-(-)-CHDA, were synthesized and intercalated with various loading amounts in the range of 19 - 26%CEC, Cation Exchange Capacity (CEC) into Lithium Taeniolite (LiTN) These pillared catalysts (Rh-Cn-(-)-CHDA/TN) were characterized by XRD, elementary analysis, and FT-IR. Results of XRD analysis showed that the clearance space of the catalyst interlayer increased proportionally with the alkyl chain length of the ligandwith the slopeof 0.14 nm/CH2.